A systematic review and meta-analysis of mindfulness- and acceptance-based interventions for affect intolerance/sensitivity. (December 2020) - Kraemer, Kristen M.; Luberto, Christina M.; Hall, Daniel L.; Ngo, Long H.; Yeh, Gloria Y.
Abstract: Affect intolerance/sensitivity, defined as one's sensitivity to, or inability to tolerate, affective states, is a transdiagnostic process implicated in the development and maintenance of numerous forms of psychopathology. Mindfulness and acceptance interventions are posited to improve affect intolerance/sensitivity; however, there has been no quantitative synthesis of this research to date. Seven electronic databases were searched up until November 2018. Hedges' g values, 95% confidence intervals, p -values, and Q -values were calculated for a series of random-effects models. Twenty-five studies (pooled N = 1778) met eligibility criteria and were included in the qualitative synthesis ( n = 22 included in the meta-analysis). There was a small, significant effect of mindfulness and acceptance interventions on improving affect intolerance/sensitivity from pre-to post-intervention (Hedges' g = −0.37, 95% CI = −0.52 to −0.23, p < .001), with effects maintained up to 6-months (Hedges' g = −0.35, 95% CI = −0.61 to −0.09, p < .01). There was a significantly larger effect for studies with inactive compared to active controls. No significant effect size differences were found for intervention length (<8 vs. ≥ 8 sessions), intervention type (mindfulness vs. acceptance) or sample type (clinical vs. non-clinical). Mindfulness and acceptance interventions modestly improve affect intolerance/sensitivity. Highlights: Affect intolerance/sensitivity is a risk factor for psychological disorders. We examined the effects of mindfulness/acceptance on affect intolerance/sensitivity. There was a small-to-medium effect size, with effects maintained up to 6 months. Control group status was a significant moderator. Mindfulness/acceptance are modestly effective for improving this target.